Sources of international law - Thirlway, H. W. A., 1937- (Oxford, United Kingdom ; New York, NY : Oxford University Press, 2014)
"The question of what is, and what is not, part of international law is of course fundamental. Traditionally, treaties between states and custom (state practice) have been seen as the primary means by which international law is created. These two sources, along with the 'general principles of law', are specified in the Statute of the International Court of Justice (Article 38), and this text has long been treated as generally authoritative. However, whether this is still an adequate definition of the sources of international law, and how they may operate in modern international society, has been questioned in significant ways. Taking Article 38 ICJ Statute as starting-point, this book provides a careful assessment of all the recognised, or asserted, sources of international law. Among the issues considered are: the impact of ethical principles on the creation of international law; the existence of peremptory norms (those of jus cogens), and whether they come into being through the same sources as other norms; the place of these, and of norms involving rights and obligations erga omnes, in the operation of international legal relationships; the definition and role of 'general principles of law'; whether any of international law's sub-disciplines involve the application of additional sources; and the continuously evolving relationship between treaty-based law and customary international law. Re-examining the traditional model, the work takes account of the increasing role of international jurisprudence, and looks at international organisations and non-state actors as potential new sources of international law. The book provides a perfect introduction to the law of sources, as well as innovative perspectives on new developments, making it essential reading for anyone studying or working in any field of international law"--Unedited summary from book jacket.
I. The nature of international law and the concept of sources -- Introduction -- Formal and material sources -- Enumeration of the recognized formal sources -- Nature and operation of the sources -- Whose law? States and non-State actors -- Are there additional sources, not in Article 38? ; Unilateral acts ; Decisions of international organizations ; Agreements between States and international enterprises ; Other proposals -- Religious law as a rival or additional source -- Is the theory of sources still sufficient? -- II. Treaties and conventions as a source of law -- Pacta sunt servanda -- The limits of treaty-law : jus cogens and the relative effect of treaties -- Commitment to the treaty-obligations -- Unilateral acts as inchoate treaties? -- III. Custom as a source of law -- Introduction -- Constituent elements of custom ; Introduction ; State practice ; The opinio juris ; The role of General Assembly resolutions -- Changes in customary law -- The relevance of ethical principles to customary law -- The 'persistent objector' -- General and local customary law -- IV. General principles of law as a source of law -- What are the 'general principles of law'? -- The role of equity -- General principles of law and non liquet -- V. The subsidiary sources -- Introduction -- Judicial decisions ; International tribunals ; Municipal courts -- The teachings of publicists -- VI. Interaction or hierarchy between sources -- Simultaneous and identical obligations under treaty and under customary law -- The 'hierarchy of sources' -- VII. Specialities : jus cogens, obligations erga omnes, soft law -- Superior norms and their sources : jus cogens and obligations erga omnes ; The source or sources of obligations erga omnes ; The source or sources of norms of jus cogens -- Soft law -- VIII. Subsystems of international law -- 'Self-contained regimes' and their limits -- Human rights law ; Human rights law under treaty and as custom ; Human rights as deriving from general principles ; Human rights and Islam -- Humanitarian law ; Treaties and conventions ; Customary law or an independent source of law? -- WTO, ICSID : trade and investment law dispute settlement -- International environmental issues -- International criminal law -- IX. Alternative approaches -- Alternatives to the traditional doctrine of sources as a whole ; Rational choice theory : Andrew T. Guzman ; Jean d'Aspremont : Formalism and the sources of international law ; Matthias Goldmann : standard instruments for the exercise of international public authority -- New approaches to customary law ; 'A new theory with practical applications' : Brian D. Lepard ; Reconciliation of 'traditional' and 'modern' approaches : Anthea Roberts -- X. Some concluding reflections.
Includes bibliographical references and index.
Keywords: International law -- Sources; International law; Droit International -- Sources; Sources